2006
DOI: 10.1097/01.icl.0000191593.87142.dd
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction and Compatibility Between a Soft Contact Lens and an Ophthalmic Drug

Abstract: These results indicated the possibility for the zwitter ionic SCL as a lens to be worn concomitantly with ophthalmic drug instillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…9 Then, it was used to assess morphologic changes and absorption of ibudilast by the lens analysis method with a dimension analyzer (Optimec, Ltd., Malvern, UK) and high-performance liquid chromatography (JASCO Corporation, Tokyo, Japan). The items evaluated for the collected lenses were the diameter after wearing, the curvature and power, the morphology, and the adsorption of ibudilast.…”
Section: Methodsmentioning
confidence: 99%
“…9 Then, it was used to assess morphologic changes and absorption of ibudilast by the lens analysis method with a dimension analyzer (Optimec, Ltd., Malvern, UK) and high-performance liquid chromatography (JASCO Corporation, Tokyo, Japan). The items evaluated for the collected lenses were the diameter after wearing, the curvature and power, the morphology, and the adsorption of ibudilast.…”
Section: Methodsmentioning
confidence: 99%
“…HA has also been investigated as a polymer device, namely, as contact lens material. Yamazaki et al . have synthesized hydrogels for use as contact lenses, which function as a type of drug delivery system technology, with sufficient amounts of drug uptake and release profiles for sterilization treatment during the perioperative period in ophthalmic areas.…”
Section: Introductionmentioning
confidence: 99%
“…HA has also been investigated as a polymer device, namely, as contact lens material. Yamazaki et al 9,10 have synthesized hydrogels for use as contact lenses, which function as a type of drug delivery system technology, with sufficient amounts of drug uptake and release profiles for sterilization treatment during the perioperative period in ophthalmic areas. Their results have indicated that the hydrogels containing side-chain ionic groups and silyl groups are useful materials for preparing drug delivery contact lenses because the drug content can be readily controlled by changing the content ratio of the ionic monomer during polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Alvarez's group reported the drug‐imprinted contact lenses which are created imprinted cavities in hydrogels for uptake drug 8, 9. We previously reported that contact lenses composed of a zwitterionic, transparent, shape‐retaining hydrogel could potentially be compatible with ophthalmic drug installation 10, 11. In addition, we have investigated contact lenses as a DDS composed of hydrogels having several ionic groups, which interact with the drugs and function as contact lenses 12, 13.…”
Section: Introductionmentioning
confidence: 99%